The Inevitable Cycle: Graphical Tools and Programming Paradigms. - Soukup, Jiri; Soukup, Martin (Computer (00189162), 2007)
Programmers keep writing programs that grow more complex until their own authors can't safely debug or modify them. At that point, those in the industry invent and use various graphical tools, and programmers resurrect the idea of programming in pictures. Then someone proposes a new paradigm or language that makes programs more manageable. With the new technology, they begin to handle more complex problems, programs grow bigger—and another cycle begins. Three cases demonstrate this cycle: Structured programming eliminated flowcharts, pointers and structures eliminated Fortran table diagrams, and object-oriented programming with class libraries eliminated the pointer diagrams popular in the 1980s.